2013
DOI: 10.1039/c3ra23391j
|View full text |Cite
|
Sign up to set email alerts
|

Single-step pyrolytic preparation of Mo2C/graphitic carbon nanocomposite as catalyst carrier for the direct liquid-feed fuel cells

Abstract: The work presented a practical and low-cost strategy for the preparation of Mo 2 C/graphitic carbon nanocomposite (Mo 2 C/GC). This synthesis has been conducted by a single-step heat treatment of resin-MoO 4 22 -[Fe(CN) 6 ] 42 precursor in N 2 atmosphere. The final material consists of well-dispersed Mo 2 C nanoparticles (typically 10-15 nm) on graphitic carbon. The formation process of Mo 2 C/GC has been investigated. The resultant material exhibits good supporting effect on Pt and Pd catalysts toward electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…The EOR can be observed on the anodic peak which was located between À0.2 and 0.1 V. It can be seen that the onset potentials were relatively similar for all samples. 9 The results also conrmed that the 20%Pd10%Ni10%Sn deposited on functionalised supports generated higher current density than those on non-functionalised supports. The 20%Pd10%Ni10%Sn/MWCNT sn exhibited the maximum current density or activity (291 mA cm À2 ) and mass activity (4288 mA mg Pd À1 ).…”
Section: Functionalisation Of Carbon-based Supportsmentioning
confidence: 81%
See 1 more Smart Citation
“…The EOR can be observed on the anodic peak which was located between À0.2 and 0.1 V. It can be seen that the onset potentials were relatively similar for all samples. 9 The results also conrmed that the 20%Pd10%Ni10%Sn deposited on functionalised supports generated higher current density than those on non-functionalised supports. The 20%Pd10%Ni10%Sn/MWCNT sn exhibited the maximum current density or activity (291 mA cm À2 ) and mass activity (4288 mA mg Pd À1 ).…”
Section: Functionalisation Of Carbon-based Supportsmentioning
confidence: 81%
“…1 There are various types of fuels being used in PEMFCs, such as hydrogen gas, formic acid, methanol, ethanol, etc. [7][8][9] High selectivity of the anode catalyst is also important as complete oxidation of ethanol to CO 2 is desired to produce the most electrons from one molecule of ethanol. The conventional hydrogen fuel cell is usually used to deliver high power density, whereas the direct methanol fuel cell (DMFC) is more suitable for low power applications.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] This adsorption mode could assist in the preferential formation of alcohols.In recent years, thanks to their unique structures and properties, advanced carbon materials such as carbon nanofibers (CNF), carbon nanotubes (CNT), and graphene have attracted a great deal of attention as possible materials for metal-free heterogeneous catalysts, [22,23] electrochemical energy storage devices, [24] and fuel cells. [25,26] In particular, graphene, a two-dimensional planar carbon material first obtained from graphite in 2004, is regarded as a promising electrocatalytic material. [27,28] Graphene can interact strongly with both transition metals and aromatic compounds: theoretical calculations and experimental results have indicated that some electron transfer may occur between the supported Pt NPs and the graphene support, [29,30] and thanks to the large p system of graphene, guest molecules with p orbitals can be adsorbed readily on its surface by p-p interactions.…”
mentioning
confidence: 99%
“…In fact, it is quite often to observe them display inspiring performances in a variety of lab-scale reactions ranging from hydrogenation to isomerization [6][7][8][9][10]. However, in industrial scale, deactivation is one big issue due to which molybdenum carbides are not yet widely applied.…”
Section: Introductionmentioning
confidence: 98%